2016
DOI: 10.1063/1.4939027
|View full text |Cite
|
Sign up to set email alerts
|

Electron injection for enhanced energy gain by a radially polarized laser pulse in vacuum in the presence of magnetic wiggler

Abstract: We present a scheme of electron injection for enhanced electron energy gain by using a radially polarized (RP) laser pulse in vacuum under the influence of magnetic wiggler. The inherent symmetry of an RP laser pulse enforces the trapping and acceleration of electrons in the direction of propagation of laser pulse during laser electron interaction. A magnetic wiggler encircles the trajectory of accelerated electron and improves the strength of v→×B→ force which supports the retaining of betatron resonance for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…However, these studies on Thomson scattering seldom address a tightly focused Gaussian laser pulse, whose transverse energy distribution is localized in a small range, and its transverse and longitudinal intensity distribution satisfies the Gaussian envelope [29,30], which is commonly used to describe the laboratory laser systems. It has been shown that for the tightly focused Gaussian laser pulse, the factors such as external magnetic field, chirped laser pulse and laser pulse polarization have significant effects on the electron acceleration [31][32][33]. In this paper, the effects of parameters of the tightly focused Gaussian laser pulses and external magnetic field on the electron dynamics and the radiation spectrum are mainly investigated.…”
mentioning
confidence: 99%
“…However, these studies on Thomson scattering seldom address a tightly focused Gaussian laser pulse, whose transverse energy distribution is localized in a small range, and its transverse and longitudinal intensity distribution satisfies the Gaussian envelope [29,30], which is commonly used to describe the laboratory laser systems. It has been shown that for the tightly focused Gaussian laser pulse, the factors such as external magnetic field, chirped laser pulse and laser pulse polarization have significant effects on the electron acceleration [31][32][33]. In this paper, the effects of parameters of the tightly focused Gaussian laser pulses and external magnetic field on the electron dynamics and the radiation spectrum are mainly investigated.…”
mentioning
confidence: 99%
“…Polarization characteristics also play a crucial role in transferring energy on laser driven charged particle acceleration. Better trapping has been investigated in case of radially polarized (RP) laser pulse [22]. It has also been noticed that higher energy gain occurs when we employ circularly polarized (CP) laser pulse in comparison with others [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the effect of chirped laser pulse and magnetic field interaction in the IFEL acceleration scheme was investigated and they showed how tightly focused chirped-pulse enhances the energy from MeV to GeV [30]. In other work, how magnetic wiggler perpetuates the resonance of betatron and enhances the energy gain (up to 4 times more) is shown [31].…”
Section: Introductionmentioning
confidence: 99%